Decoloniality and methodologies of knowledge production in Social Work: The resurgence of the systematization of social experiences and practices - Ruiz-Muñoz, Isaac Francisco (Prospectiva. Revista de Trabajo Social e Intervención Social, 2026)
In this article a reflection is made about the coloniality of knowledge and its impact on hegemonic forms of knowledge production within the field of Social Work. From a decolonial perspective, the neoliberal and Eurocentric academic rationality is problematized, which defines the criteria of scientific validity, hierarchizes epistemologies, and marginalizes situated knowledges emerging from professional practice. It aims to recover the systematization of experiences and social practices as a critical methodology historically linked to the identity of Latin American Social Work—which allow not only to understand practices, but also the production of ethical, political, and transformative knowledge. Through the theoretical review the tensions among university, academia, and discipline are analyzed. It also presents a discussion of methodological principles structured in phases, foundations, and tools that enhance systematization as an epistemic counter-hegemonic strategy. Finally, a reading is proposed that explains under which conditions systematization can operate as a counter-hegemonic epistemic strategy in Social Work—not because of the method itself but through its ethical-political orientation, the legitimacy dispute that it sustains, affirming it as a situated way to produce critical knowledge from practice.